2006
DOI: 10.5039/agraria.v1i1a308
|View full text |Cite
|
Sign up to set email alerts
|

Decomposição de resíduos vegetais de espécies da Caatinga, na região de Patos, PB

Abstract: Decomposição de resíduos vegetais de espécies da Caatinga, na região de Patos, PB RESUMO Estudar a dinâmica de decomposição de resíduos vegetais de diferentes espécies da caatinga e avaliar a atividade microbiana na região semi-árida da Paraíba, é o ponto que norteia este trabalho. A área de estudo localizou-se no município de Patos, PB, com clima do tipo Bhs, definido como semi-árido quente e seco, com estação seca bem definida temperatura média de 28,8º C, altitude de 270 m e precipitações médias de 400 mm. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 4 publications
1
4
0
5
Order By: Relevance
“…The litterfall fractions distribution pattern at the 30-year stand was similar to that found by Alves et al (2006) and Andrade et al (2008) in Caatinga fragments: leaves > branches/twigs > reproductive structures > others. While Lopes et al (2009) obtained a distribution similar to the stands of 15 and 50 years: leaves > reproductive structures > branches/twigs > others.…”
Section: Discussionsupporting
confidence: 86%
“…The litterfall fractions distribution pattern at the 30-year stand was similar to that found by Alves et al (2006) and Andrade et al (2008) in Caatinga fragments: leaves > branches/twigs > reproductive structures > others. While Lopes et al (2009) obtained a distribution similar to the stands of 15 and 50 years: leaves > reproductive structures > branches/twigs > others.…”
Section: Discussionsupporting
confidence: 86%
“…Costa et al (2005) studied nutrient decomposition and nutrient release by tree litter in a Eucalyptus grandis stand and concluded that there was higher decomposition rate during the wettest rainfall period. Appropriate conditions of soil moisture and temperature increase microbial activity and enhance decomposition rate (Alves et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Para a determinação da decomposição foliar foram coletadas amostras da fração foliar de Gliricídia sepium, espécie leguminosa usada na adubação verde e alimentação animal, adaptada a regiões semiáridas e de brejos. A escolha da espécie se deu pela baixa resistência a decomposição (Alves et al, 2006). As folhas foram colocadas em estufa de circulação de ar forçada a 65 °C até atingir peso constante, e posteriormente, para estimativa da decomposição, foram pesadas porções de 10 g da folha seca e acondicionadas em bolsas de nylon (litterbags) de malha 2 mm e dimensões 20 × 30 cm conforme metodologia proposta por Wieder (1982) e Olson (1963).…”
Section: Decomposição Da Fitomassaunclassified